Strategies and practices of advocacy: Gender advocacy against trafficking in women in Nepal - Poudel, Meena; Luintel, Youba R (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,626 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v8i0.1121 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.59-76